Board characteristics and the insolvency risk of non-financial firms - Florian Maier; B. Burcin Yurtoglu (Journal of Risk and Financial Management, 2022)
How do board characteristics influence the risk of bankruptcy? We study this question by estimating classic Z-Score models using panel data comprising 2519 listed non-financial firms from 29 European countries over the 2012-2020 period. We found that board independence is associated with lower risk of bankruptcy. In contrast, employee representatives have an adverse effect on board monitoring capacity and are predicted to increase bankruptcy risk. The presence of female directors and foreign directors on board-two indicators of board diversity-reduce bankruptcy risk. While board independence and diversity decrease bankruptcy risk in financially non-distressed firms, they have the opposite effect in financially distressed firms. These findings are statistically and economically significant and hold, at least in part, under alternative specifications. Our findings demonstrate the need for governance regulators, credit rating agencies, financial institutions, firms and investors to lend more weight to board composition, especially under the conditions of impending financial distress.
Keywords: 650; corporate governance; bankruptcy risk; board diversity; board independence; Europe